Radiological Safety Assessment of Agricultural Soil within the Bitumen Belt of Ondo State Nigeria, Using RESRAD-ONSITE and RESRAD-BIOTA Codes - Luka S. Yani; Gregory O. Avwiri; Chinyere P. Ononugbo (Archives of Current Research International, 2023)
Exploration and exploitation of bitumen can create radiation exposure pathways that must be considered in risk management scenarios. RESRAD-ONSITE and RESRAD-BIOTA developed by the US Department of Energy (US DOE) to assess contaminated sites, were used in the present study to predict the radiation dose and excess cancer risk associated with residual radioactive materials within Ondo State Bitumen Belt for the duration of 100 years, using site-specific parameters. The activity concentrations of 40K, 232Th and 238U in soil samples were determined by gamma-spectrometry and their average values were 35.85, 3.27 and 5.01 BqKg-1 respectively. While the estimated internal doses in biota due to 40K, 232Th and 238U were 7.54E-06, 3.03E-07 and 4.55E-08 Gy d−1 respectively for terrestrial animals, 6.69E-06, 3.68E-08 and 2.29E-08 Gy d−1 respectively for terrestrial plants, 6.49E-06, 5.88E-09 and 2.22E-08 08 Gy d−1 respectively for the Nigerian Dwarf Goat (NDG). The maximum total dose of 0.0229 mSvyr−1 was obtained at Agbabu at t = 30 years for an on-site resident farmer using the RESRAD-ONSITE Code, while the minimum total dose of 0.0014 was obtained at Araromi at t = 100 years. These values were by far lower than the National Research Council’s acceptable limit of 0.25 mSvy-1. Likewise, the maximum Excess Cancer Risk (ECR) of 0.050 × 10−3 was obtained at Agbabu, while the lowest ECR value of 0.015 x 10-3 was shared by three communities: Omotosho (OMO), Akotogbo (AKG), and Ibekegbo (IKB). The observed low cancer risks in all the selected communities are of less human health concern since they are lower than the world safe value of 0.29 x 10-3. This implies that utilization of the studied soil for farming may not cause any immediate health hazard to the inhabitant but prolonged exposure might pose radiologically induced health challenges.